2022
DOI: 10.3389/fnagi.2022.951197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 6-RBP gene signature for a comprehensive analysis of glioma and ischemic stroke: Cognitive impairment and aging-related hypoxic stress

Abstract: There is mounting evidence that ischemic cerebral infarction contributes to vascular cognitive impairment and dementia in elderly. Ischemic stroke and glioma are two majorly fatal diseases worldwide, which promote each other's development based on some common underlying mechanisms. As a post-transcriptional regulatory protein, RNA-binding protein is important in the development of a tumor and ischemic stroke (IS). The purpose of this study was to search for a group of RNA-binding protein (RBP) gene markers rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 156 publications
(186 reference statements)
0
5
0
Order By: Relevance
“…There were some relevant studies in favor of this relationship, and there would be some mechanisms involved (32). A study reported that stroke was associated with cognitive impairment and dementia in older adults, and the six RNA-binding protein (RBP) genes (POLR2F, DYNC1H1, SMAD9, TRIM21, BRCA1, and ERI1) might participate in the process by mediating the hypoxic responses and angiogenesis (33). Regarding cardiovascular diseases and memory function, studies jointly found that better cardiovascular health is associated with lower memory decline and risk of cognitive impairment (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…There were some relevant studies in favor of this relationship, and there would be some mechanisms involved (32). A study reported that stroke was associated with cognitive impairment and dementia in older adults, and the six RNA-binding protein (RBP) genes (POLR2F, DYNC1H1, SMAD9, TRIM21, BRCA1, and ERI1) might participate in the process by mediating the hypoxic responses and angiogenesis (33). Regarding cardiovascular diseases and memory function, studies jointly found that better cardiovascular health is associated with lower memory decline and risk of cognitive impairment (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic tools have become increasingly popular with the rapid development of high-throughput technology for assessing prognostic markers and studying mechanisms ( Wei et al, 2019 ; Shi et al, 2021 ; Luo et al, 2022a ; Luo et al, 2022b ; Chen et al, 2022 ; Lin et al, 2022 ; Mei et al, 2022 ; Xuan et al, 2022 ; Zhao and Jiang, 2022 ). In melanoma, lung cancer, and renal clear cell carcinoma, cuproptosis-related genes have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Predictive models can also assist physicians in implementing precision medicine, thereby formulating more personalized and efficacious treatment plans ( Pencina & Peterson, 2016 ; Obermeyer & Emanuel, 2016 ; Kang et al, 2020 ; Wu et al, 2021 ; Lin et al, 2022 ; Chen et al, 2022a ). These models can enhance research efficiency, accelerate the development of novel pharmaceuticals, and optimize therapeutic strategies, ultimately making significant contributions to the improvement of human health.…”
Section: Introductionmentioning
confidence: 99%